2002
DOI: 10.1073/pnas.222536599
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans are a potential cause of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, and inflammatory disease of connective tissue with unknown etiology. We investigated whether aberrant immune responses to glycosaminoglycans (GAGs), a major component of joint cartilage, joint fluid, and other soft connective tissue, causes this disease. Here we show that injection of GAGs such as hyaluronic acid, heparin, and chondroitin sulfates A, B, and C induce arthritis, tendosynovitis, dermatitis, and other pathological conditions in mice. We developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 34 publications
4
80
0
1
Order By: Relevance
“…Cell culture experiments consistently showed that DS was the most potent in stimulating cell proliferation, whereas others had much lower activity. This observation was in agreement with our earlier assessment 14 and later reports. 15,16 The proliferative effect of DS was dose dependent, and concentrations of 20 g/mL or higher significantly stimulated cell proliferation.…”
Section: Ds Stimulates Cd5 ϩ B-cell Proliferationsupporting
confidence: 94%
See 1 more Smart Citation
“…Cell culture experiments consistently showed that DS was the most potent in stimulating cell proliferation, whereas others had much lower activity. This observation was in agreement with our earlier assessment 14 and later reports. 15,16 The proliferative effect of DS was dose dependent, and concentrations of 20 g/mL or higher significantly stimulated cell proliferation.…”
Section: Ds Stimulates Cd5 ϩ B-cell Proliferationsupporting
confidence: 94%
“…14 We then determined that DS potently stimulates B-cell proliferation (Figure 1; see also Supplemental Figure S1 at http://ajp.amjpathol.org) and production of immunoglobulin, particularly IgM, in vitro. These findings are in agreement with published results.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of OPN also is a risk factor for the development of autoimmunity and lymphoproliferative disorders (63). Furthermore, experimental administration of GAGs, including HA, chondroitin sulfates (A, B, and C), and heparin, all natural ligands of CD44, induce autoimmune connective tissue disease in normal mice (55,64). Interestingly, a majority of the pathogenic inflammatory cells in this study are CD4 ϩ , GAG-binding T cells, consistent with an NKT cell population.…”
Section: Discussionsupporting
confidence: 60%
“…Although HA has been considered to be unequivocally beneficial by many physicians, there are clear signs that HA degradation products exert a series of unwanted effects (4,26,27). The strongest support for our working hypothesis that unfettered HA might be detrimental in RA came from an animal study demonstrating that prolonged injection of HA in healthy animals can cause all of the classical signs of RA (28). In addition to many clinical reports questioning the practice of HA injections, another animal study designed to demonstrate the beneficial effects of HA injections also provides evidence of potentially profound adverse effects of such measures (29).…”
Section: Discussionmentioning
confidence: 89%